Mining Urban Data (Part B). (April 2016) - Andrienko, Gennady; Gunopulos, Dimitrios; Ioannidis, Yannis; Kalogeraki, Vana; Katakis, Ioannis; Morik, Katharina; Verscheure, Olivier
Abstract: Modern cities are flooded with data. New information sources like public transport and wearable devices provide opportunities for novel applications that will improve citizens׳ quality of life. From a data science perspective, data emerging from smart cities give rise to a lot of challenges that constitute a new interdisciplinary field of research. This article introduces the second part of a special issue on the topic 'Mining Urban Data' published in the journal Information Systems.